Pelatihan deteksi dini penyakit tidak menular pada kader Posbindu di wilayah kerja Puskesmas Sekip Kota Palembang - Emma Novita; Achmad Ridwan; Bahrun Indawan; Eddy Roflin; Kemala Andine P (Fakultas Kedokteran Universitas Sriwijaya, 2020)
Globally, WHO (World Health Organization) estimates that non-communicable diseases cause about 71% of all deaths worldwide. Data for 2018 in Indonesia shows an increase in the prevalence of non-communicable diseases such as cancer, stroke, chronic kidney disease, diabetes mellitus and hypertension compared to the previous five years. Currently, the Indonesian Ministry of Health has implemented an early detection and prevention program for non-communicable diseases in the community by carrying out promotional, preventive, curative and rehabilitative activities for individuals and communities through Posbindu PTM in schools, workplaces, prisons / remand centers, terminals, fishing villages. The training was carried out by the FK UNSRI team as a community service activity, with 10 participants from Puskemas Sekip and 12 participants from FK UNSRI. The objective of the training is that participants are able to manage and implement the Non-Communicable Disease (PTM) Posbindu. The material provided by the methods of lectures, question and answer, discussion, skill practice, namely providing knowledge about PTM, Posbindu PTM, providing abilities & skills in monitoring PTM risk factors and counseling. There is a significant increase in posttest scores compared to pretest, which means that there is an increase in knowledge and skills of early detection of risk factors for PTM. This activity initiated the formation of the Posbindu PTM FK Unsri.